Wimer Bedford papers - Bedford, Wimer, 1835-1905.
Diaries (3 volumes; 1864 Jan. 9-1865 July 9) including descriptions of the siege of Vicksburg, Miss., and Sherman's march to the sea. An essay, copied by Cornelia E. Bedford with a foreword by her, is entitled "Real Life in the Civil War" and relates to incidents in Bedford's career (1861-1865).
Captain and assistant adjutant general of volunteers, U.S.
Collection material in English.
Keywords: Bedford, Cornelia E; Sherman's March to the Sea; Mississippi -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; Vicksburg (Miss.) -- History -- Siege, 1863.; Army officers